Bahasa Inggris: Bahasa Inggris - Riah Wiratningsih (FPPTI Jawa Tengah, 2021)
This article aims to share the academic librarian's experiences providing consultation services to library users during Indonesia's Covid-19 pandemic since March 2020. Further, it describes the academic librarian's challenges in developing countries to meet the academic community’s demands. The approach used is the author's personal experiences as an academic librarian. The data were taken from students' questions on personal communication by WhatsApp and Email, then reviewed by the author to find solutions. A review of current literature about the topic deals with issues presented scientifically. This paper's results explain academic librarians' efforts in carrying out their roles during the Covid-19 pandemic. The attempts implemented in the central library of Universitas Sebelas Maret enhance library website content and online consultation services. This article is expected to contribute valuable insight and practical solutions regarding virtual assistance to help students develop their skills and become self-learners during the pandemic.